The The Role of Regional Tax Management in Supporting the Increase of Local Own-Source Revenue at Bapenda UPTB 3 Surabaya - Putri, Aldhila Shafira; Sri Trisnaningsih (International Journal of Economics and Management Sciences, 2026)
This study aims to evaluate the contribution of Land and Building Tax (PBB) management to increasing Local Own-Source Revenue (PAD) at Bapenda UPTB 3 Surabaya, with a focus on the role of digital transformation in tax collection. The study examines regional tax management supported by taxpayer compliance, system digitalization, and efficient collection mechanisms. A descriptive qualitative method with a case study approach was employed. Data were collected through direct observation, interviews, and documentation conducted during a five-month internship period at Bapenda UPTB 3 Surabaya. The findings reveal that effective PBB management contributes significantly to improving collection efficiency and strengthening local revenue generation. The implementation of digital systems has facilitated tax administration, enhanced monitoring processes, and encouraged higher taxpayer compliance. However, several operational challenges remain, particularly in optimizing system utilization and human resource competencies. Therefore, policy efforts should prioritize accelerating digital transformation and enhancing staff capacity to support sustainable improvements in regional tax administration and PAD growth.